Neck pain and associated factors in a sample of high school students in the city of Bauru, São Paulo, Brazil: cross-sectional study - Vitt, Alberto de; Bento, Thiago Paulo Frascareli; Perrucini, Priscila de Oliveira; Felippe, Lilian Assunção; Poli-Frederico, Regina Célia; Borghi, Sergio Marques (São Paulo Medical Journal, 2021)
BACKGROUND: Neck pain is a major public health problem. OBJECTIVE: The aim of the present study was to determine the prevalence of neck pain among high school students and to analyze associations with sociodemographic variables, use of electronic devices, habitual physical activity practices and mental health problems. DESIGN AND SETTING: Cross-sectional epidemiological study on a sample of high school students in the city of Bauru, São Paulo, Brazil. METHOD: Participants were selected through cluster sampling in two stages and data were collected via face-to-face interviews. Data collection comprised the following steps: 1. sociodemographic characteristics; 2. use of electronic devices; 3. habitual physical activity levels; 3. mental health; and 4. neck pain. RESULTS: A total of 1,628 participants were interviewed. The prevalence of neck pain was 49.1% (95% confidence interval, CI 46.7 to 51.5), with 40.4% (95% CI 37.0 to 43.7) in men and 57.5% (95% CI 54.2 to 60.9) in women. The variables associated with in neck pain were: female (prevalence ratio, PR = 2.04), use of cell phone in standing posture (PR = 1.47), use of tablet in sitting posture (PR = 1.72), length of computer use greater than 3 hours/day (PR = 1.54), length of cell phone use greater than 3 hours/day (PR = 1.54), length of tablet use greater than 3 hours/ day (PR = 1.34) and mental health problems (PR = 1.56). CONCLUSION: There is high prevalence of neck pain among students and striking associations with female sex, use of electronic devices and mental health problems